Processing and Polyherbal Formulation of Tetradium ruticarpum (A. Juss.) Hartley: Phytochemistry, Pharmacokinetics, and Toxicity - Shan, Qi-yuan; Sang, Xia-nan; Hui, Hui; Shou, Qi-yang; Fu, Hui-ying; Hao, Min; Liu, Kao-hua; Zhang, Qiao-yan; Cao, Gang; Qin, Lu-ping (Frontiers in Pharmacology, 2020)
Herbal medicine is a major part of traditional Chinese medicine (TCM), which is evolved as a system of medical practice from ancient China. The use of herbal medicine is mainly based on practice and theories and concepts rooted in ancient philosophy. In the era of evidence-based medicine, it is essential to accurately evaluate herbal remedy with standard/modern medical practice approaches. Tetradium ruticarpum (A. Juss.) Hartley (TR), a medicinal plant with diversify bioactive components, has been broadly used to treat pain and gastrointestinal disorders in TCM. However, TR has also been reported to have potential toxicity by long-term use or excessive doses, though the associated compounds are yet to be identified. TR is usually processed, and/or combined with other herbs in TCM formulas in order to achieve a synergistic effect or reduce its toxicity. Since processing or polyherbal formulation of TR may lead to changes in its chemical composition and contents, quality, efficacy and toxicity, comparison of TR samples before and after processing, as well as its combination with other medicines, would provide useful knowledge of bioactive compounds, efficacy and toxicity of this valuable medicinal plant. Here we reviewed the recent studies about the phytochemistry, pharmacokinetic behaviors and toxicity of TR under various processing or polyherbal formulation conditions, which would expand our understanding of mechanisms of TR’s efficacy and toxicity and be valuable for quality control in industrial manufacturing, future medicinal research, and safety and rational use of TR in TCM.